PHARMACOKINETICS OF KETOPROFEN IN HEALTHY BUFFALO CALVES IN PAKISTAN - Z. U. Rehman; M. Ashraf; M. A. Khan; M. A. Jabbar M. Abbas; A. M. Khan (Journal of Animal and Plant Sciences, 2013)
The present research project was designed to study the pharmacokinetics of Ketoprofen (KTP), a non-steroidal antiinflammatory drug (NSAID) in local healthy buffalo calves. For this purpose, eight healthy buffalo calves were administered, a single intravenous bolus of KTP at the dose of 3.0 mg/kg body weight through jugular vein. Blood samples (3-5ml) were drawn in heparinized vacutainers, pre-medication at zero-hr, and then at 0.08, 0.17, 0.25, 0.5, 0.75, 1.0, 2.0, 3.0, 4.0, 6.0, 8.0, 10.0, 12.0, 24.0, 48.0, 60.0, 72.0, 84.0, 96.0 hrs post medication. The plasma was separated by centrifugation at 4000 rpm for 10 minutes and stored at−80°C till analyzed. The concentration of KTP in plasma was determined through a standardized HPLC (high performance liquid Chromatography) method. The concentration -time profile of KTP of each animal was prepared semi-logarithmically. The plasma concentration-time data was analyzed by a computer based pharmacokinetic software, APO, Version 3.02, and the pharmacokinetic parameters of ketoprofen in buffalo calves were calculated as Mean ± SEM, AUC (Area Under Curve) 14.42 ± 1.97 µg.h/ml, Cl (Clearance) 0.19 ± 0.025 l/hr/kg, t½ (Half Life) 3.58 ± 0.418 hr, VD (Volume of Distribution) 0.985 ± 0.175 l/kg, VDss (Volume of distribution at Steady State) 0.551 ± 0.0895 l/kg, and Kel (Elimination Rate Constant) 1.46 ± 0.196 l/hr, respectively.
Keywords: HPLC; Ketoprofen; NSAID; Pharmacokinetics; Intravenous administration